Emerging Trends in Rural Governance: A Bibliometric Analysis of Policies and Strategies for Developing Underprivileged Villages - Yandri Susanto; Suwarno Suwarno; Benny Hutahayan (Lex Publica, 2024)
This study investigates emerging trends in rural governance, focusing on policies and strategies for the development of underprivileged villages. A bibliometric analysis of relevant publications from 2020 to 2024 was conducted to identify key patterns and trends in rural governance research. The findings highlight the significance of decentralization, community empowerment, and participatory governance in enhancing rural development. Key challenges, such as poverty, geographic isolation, and limited infrastructure, are emphasized as barriers to sustainable growth in underprivileged villages. The study also explores the role of leadership, stakeholder engagement, and digital technologies in improving governance capacity. A holistic approach integrating evidence-based policy-making, local community involvement, and technological advancements is recommended to address these challenges. The research offers insights into the global context of rural governance, with Indonesia emerging as a key focus for development strategist.